2019
DOI: 10.33314/jnhrc.v17i3.1789
|View full text |Cite
|
Sign up to set email alerts
|

Health Related Quality of Life of Children with Congenital Heart Disease Attending at Tertiary Level Hospital

Abstract: Background: Congenital heart disease is one of the common congenital anomaly among the children affecting growth and development of the child and increasing susceptibility of the child to failure to thrive. The objective of the study is to find out the overall health related quality of life of children with congenital heart disease.Methods: A descriptive cross sectional study was carried out among 150 children with congenital heart disease attending in the pediatric out-patient department of Shahid Gangalal Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Furthermore, a sense of uncertainty about the child’s circumstances often causes anxiety and depression in parents, and these negative emotions indirectly affect the child’s physical, emotional, and social functioning. This anxiety in parents can lead to overprotection of the children, reducing the children’s opportunities for contact and communication with the outside world and thus affecting their social and psychological adaptability, thereby reducing the HRQL levels ( 33 , 34 ). After occlusion, with the alleviation of the disease, the outlook of both parents and children tended to improve, creating a healthy and positive environment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a sense of uncertainty about the child’s circumstances often causes anxiety and depression in parents, and these negative emotions indirectly affect the child’s physical, emotional, and social functioning. This anxiety in parents can lead to overprotection of the children, reducing the children’s opportunities for contact and communication with the outside world and thus affecting their social and psychological adaptability, thereby reducing the HRQL levels ( 33 , 34 ). After occlusion, with the alleviation of the disease, the outlook of both parents and children tended to improve, creating a healthy and positive environment.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have targeted the HRQOL of children with CHD, but findings are still heterogeneous. Some authors reported higher HRQOL in adolescence for those with CHD [ 19 , 28 ], while others found their HRQOL to be impaired compared to typically developing adolescents [ 30 , 31 ]. In our study of primary school-aged children [ 50 ], we found a trend in mothers of children with a VSD: mothers reported higher HRQOL in their children than the control group (child self-rating did not differ between groups).…”
Section: Aims Of This Studymentioning
confidence: 99%
“…Nevertheless, results on the perceived HRQOL of children with CHD are still inconsistent. Some studies reported satisfactory overall HRQOL with no differences or even better scores compared to non-affected controls [ 19 , 27 , 28 , 29 ], whereas other studies found these children to be at a greater risk of impaired HRQOL [ 30 , 31 , 32 ]. These differences could be attributed to variability in method designs, such as the age of the children at the time of assessment [ 33 ] or the severity of CHD [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, there were no significant differences in the self-rated quality of life scores of children in different age groups, but the scores were slightly higher in the 5–7 years old group than in the 8–12 years old group. The reason is that there is a certain correlation between the quality of life and the level of children's growth and development [ 18 ]. 8–12 year olds have increased analytical and comprehension skills and have made significant psychological transitions during this period.…”
Section: Discussionmentioning
confidence: 99%